Spotlight on graduate student Hazrulrizawati Abd Hamid, PhD (Industrial Chemistry) candidate - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Chin, Mei Lee; Norhayati, Nordin; Siti Aisah, Harun; Nenie Zuryati, Abdullah; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras (Penerbit Universiti Malaysia Pahang, 2011)
Hazrulrizawati Abd Hamid ,29 years old was born in Ked a h. She received her early education in A lor Setar and pursued her BSc in Chemistry Education at Universiti Teknologi Malaysia, Skudai Johor.